Perceived Knowledge, Attitude and Practice of Dental Students at University of Washington School of Dentistry Regarding the Diagnosis and Management Strategies of Temporomandibular Disorders. - Kaur, Amarinder (My University, 2025)
BACKGROUND:-Temporomandibular Disorders (TMD) represent a group of conditions that impact the temporomandibular joint (TMJ), the muscles of mastication, and associated structures, frequently resulting in pain, dysfunction, and diminished quality of life. TMD is prevalent in the global population with up to 10% of individuals exhibiting symptoms. Despite its common occurrence, the diagnosis and treatment of TMD is difficult due to the disorders’ complex nature which encompass both physical and psychosocial elements. Dental students are trained to recognize the clinical manifestations of TMD, evaluate potential etiologies, and propose suitable therapeutic approaches during their dental education. The perceived knowledge, attitude, and practice (KAP) of dental students concerning TMD is a vital area of investigation to help assess their preparedness to manage the disorder in clinical settings.  Objectives: To evaluate the level of perceived knowledge of dental students regarding the causes, clinical presentation, and diagnosis of TMD. To determine the attitude of dental students towards diagnosing and treating TMD in clinical practice. To determine the anticipated practices of dental students towards diagnosing and treating TMD in future clinical practice. Methods: Anonymous self-administered cross-sectional survey with closed and open-ended questions which included all 3rd and 4th year University of Washington dental students who had completed at least 6 months of clinical training and at least 2 quarters in a clinical clerkship that trains students in the diagnosis and management of TMD. Results: The survey was conducted between 3rd and 4th year dental students. Seventy-five out of 145 recruited students responded to the survey. It was observed that 82.7% students self-reported understanding of the potential causes and risk factors of TMD and 86.7% reported ability to recognize the common symptoms associated with TMD.Nearly 94.7% believed that patients with jaw, face or neck pain should be screened for TMD, 96% believed TMD has a negative impact on patients’ quality of life, and 81.3% believed that TMD represents a public health concern. Conclusion: This study indicates that dentistry students at the University of Washington display a high perceived knowledge and predominantly consistent attitude towards the management of temporomandibular disorders; however, students expressed only modest perceived expertise in TMD management likely indicating constrained clinical confidence.
Thesis (Master's)--University of Washington, 2025
Keywords: Attitude; Biopsychosocial; Occlusal Equilibration; Perceived Knowledge; Survey; TMD; Dentistry; Dentistry